Application of the social being program to develop emotional intelligence in teachers - Arratea Berrospi, Fanny R. (2021)
Conscious that all research must have a logical coherence, we define the general objective with the following statement: Establish the epistemological perspective of mathematics as the foundation of science. Lines later we determine the type of research, was fundamental or basic, the reason, our purpose is to deepen and increase, as much as possible, generate knowledge about the epistemology of mathematics and mathematics as the foundation of science. Near the epilogue of the study we arrive at the following result: Mathematics is the foundation of the sciences, because it is the language of nature, of the cosmos, both are expressed only through mathematics, also because measurement is a basic factor for the construction of scientific knowledge, discover new theories and laws. Finally we came to the conclusion: It was established that mathematics is the foundation of the sciences, essentially of the natural sciences and to a lesser extent of the social sciences. Philosophy has a reflexive relationship with mathematics and mathematics from an epistemological perspective are the object of scientific research.